2004
DOI: 10.1080/13488678.2004.10801141
|View full text |Cite
|
Sign up to set email alerts
|

The Linguistic Features of Complaint Letters to Editors in Philippine English and Singapore English

Abstract: Philippine English and Singapore English are legitimate varieties of Southeast Asian English and indeed affirm the pluralism of English. This paper examines selected linguistic features of these two varieties of English as reflected in complaint letters to editors of newspapers. The linguistic properties examined include grammatical and lexical features such as personal reference pronouns, modal verbs, and attitudinal/evaluative adjectives; a syntactic feature in terms of the passive; speech act verbs in terms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…Differences in complaint strategies and expression were studied across cultures (Cohen and Olshtain, 1993) and socio-demographic traits (Boxer, 1993a). In naturally occurring text, the discourse structure of complaints has been studied in letters to editors (Hartford and Mahboob, 2004;Ranosa-Madrunio, 2004). In the area of linguistic studies on computer mediated communication, Vásquez (2011) performed an analysis of 100 negative reviews on TripAdvisor, which showed that complaints in this medium often co-occur with other speech acts including positive and negative remarks, frequently make explicit references to expectations not being met and directly demand a reparation or compensation.…”
Section: Related Workmentioning
confidence: 99%
“…Differences in complaint strategies and expression were studied across cultures (Cohen and Olshtain, 1993) and socio-demographic traits (Boxer, 1993a). In naturally occurring text, the discourse structure of complaints has been studied in letters to editors (Hartford and Mahboob, 2004;Ranosa-Madrunio, 2004). In the area of linguistic studies on computer mediated communication, Vásquez (2011) performed an analysis of 100 negative reviews on TripAdvisor, which showed that complaints in this medium often co-occur with other speech acts including positive and negative remarks, frequently make explicit references to expectations not being met and directly demand a reparation or compensation.…”
Section: Related Workmentioning
confidence: 99%